Demokrasi dalam pluralitas: refleksi hegemoni barat-Islam - Muh. Zuhri (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2010)
In pluralistic society, democracy has become the best solution for respecting human rights dan giving thefreedom of expression. Normatively, democracy could solve any social-political issues through majorityvoices. Even though, Islam has not mention the term of democracy, its basic tenets teaches thathumankind is equal before God; and it teaches that the nobility of humankind depends on  theirproximity and nearness to God. Islam explicitly forbids the believe in that one nation to claim theirsuperiority than the others. In Islam, syura has the significant role of solving any kinds of problem inliving together.  Thus, democracy in principle did not transgress the Islamic teaching on humanism. Onthe contrary, sectarianism has created negative sentiment and conflict between East and West whichapparently represented by United States and Middle East. Through their sophisticated camouflage theUnited States has accused almost Islamic countries   as the hotspot of terrorism, even thought theirindictment has been factually wrong and misguided.